Soil health recovery after grassland reestablishment on cropland: The effects of time and topographic position. Issue 2 (8th April 2020) - De, Mriganka; Riopel, Jason A.; Cihacek, Larry J.; Lawrinenko, Michael; Baldwin‐Kordick, Rebecca; Hall, Steven J.; McDaniel, Marshall D.
Abstract: The Conservation Reserve Program (CRP) is a U.S. federal land conservation program that incentivizes grassland reestablishment on marginal lands. Although this program has many environmental benefits, two critical questions remain: does reestablishing grasslands via CRP also result in soil health recovery, and what parts of restored fields (i.e., topographic positions) recover the fastest? We hypothesized that soil health will recover over time after converting cropland to CRP grassland and that recovery will be greatest at higher topographic positions. To test this, we sampled 241 midwestern U.S. soils along a grassland chronosequence (0–40 yr, including native grasslands) and at four topographic positions (i.e., a chronotoposequence). Soils were measured for bulk density, maximum water holding capacity (MWHC), soil organic C (SOC), extractable inorganic N, potentially mineralizable C (PMC), and N. Native grasslands had superior soil health compared with cropland and most CRP soils, and even 40 yr since grassland reestablishment was not adequate for full soil health recovery. Topographic position strongly influenced soil health indicators and often masked any CRP effect, especially with MWHC and SOC. However, PMC (a measure of active C) responded most rapidly to CRP and consistently across the landscape and was 26–34% greater 19–40 yr after grassland reestablishment. Reestablishing grasslands through CRP can improve soil health, although topographic position regulates the recovery, with greatest improvements at shoulder slope positions. Patience is needed to observe changes in soil health, even in response to a drastic management change like conversion of cropland to CRP grassland.